Sistem Pendeteksi Keamanan Ruangan “Smart Security” Dengan Metode Fuzzy Logic Menggunakan Sensor PIR Berbasis Internet of Things (IoT) - Rima Tamara Aldisa; Sechan Alfarisi (Jurnal Sistem Komputer dan Informatika (JSON), 2022)
The system is an attempt to assist in detection using sensors, an effort made for a room or house if people come or enter. A tool is designed that can be easy, affordable and can be used to prevent the danger of unknown people from entering the room or even into our homes. The author designed a "Smart Security" Room Security Detection System Using the Fuzzy Logic Method Using Internet of Things (IoT)-Based PIR Sensors. sending messages if someone enters the room or house so that the owner knows if someone is unknown. The author wants to design and make this tool that can be very helpful for use inside or at home in order to minimize the danger of people who cannot be recognized entering, room security detectors here with a distance of 1 cm to 2 meters the sensor can still be detected, if it exceeds 2 meter then the sensor will not read if anyone comes.